Olusola : an icon of man's humanity to man - Kolawole, O'femi (Ogba, Nigeria Posterity media books, 2010)
The book is a biography of Segun Olusola. Series of interviews were held with him at his home in Surulere, Lagos, to get several details about his life as well as scanning through private documents, newspaper clippings and library archives.
The definitive biography of Africa's first television producer.
Includes index
nmn 01/08/18
Loans
Keywords: Biography; Biography - Olusola; Olusola Segun